The Economic Impact of AIDS Treatment : Labor Supply in Western Kenya - Thirumurthy, Harsha; Graff Zivin, Joshua; Goldstein, Markus (2012)
Using longitudinal survey data collected in collaboration with a treatment program, this paper estimates the economic impacts of antiretroviral treatment. The responses in two outcomes are studied: (1) labor supply of treated adult AIDS patients; and (2) labor supply of individuals in patients' households. Within six months after treatment initiation, there is a 20 percent increase in the likelihood of the patient participating in the labor force and a 35 percent increase in weekly hours worked. Young boys in treated patients' households work significantly less after treatment initiation, while girls and adult household members do not change their labor supply.